Mandibular ameloblastoma reconstruction: a case report with 10-year follow-up - Villanueva-Maffei, Julio Alberto; Dallaserra-Albertini, Matías; Domancic-Alucema, Stefan; Zamorano-Young, Gabriel; Zapata-Baeza, Sebastián (Revista Facultad de Odontología Universidad de Antioquia, 2019)
Ameloblastoma is a benign dental tumor mostly found in the mandible, with several variations. The treatment of this pathology ranges from simple enucleation to resection of large sections of the affected bone. There are several options for correcting the sequelae of ameloblastoma treatment, including the use of grafts and currently microvascular free flaps, which have become the standard treatment. This report describes a clinical case of a large mandibular ameloblastoma, which was resected with safety margins about 10 years ago, reconstructed by free grafts in successive surgical times and rehabilitated using removable prostheses. The question is then what the best option is today in the reconstruction of patients affected by this type of pathologies, taking into account emerging options, the clinicians’ learning curve and the patients’ resources.